HUBUNGAN PEMBERIAN MAKANAN PENDAMPING AIR SUSU IBU (MP-ASI) DENGAN STATUS GIZI BAYI USIA 6-12 BULAN DI WILAYAH KERJA PUSKESMAS KETUWAN, KECAMATAN KEDUNGTUBAN KABUPATEN BLORA, JAWA TENGAH - , VINDA DWI HANIFAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: The high rate of infant and child mortality is a common characteristic in countries that are developing, including Indonesia. One cause that stands out among others because of poor nutritional status. The first six months is a very critical period in the life of a toddler. One of the problems in infant feeding is the cessation of breastfeeding and complementary feeding is not giving sufficient in quantity and quality. The results of research on the relationship giving complementary feeding and nutritional status showed diverse relationships. The prevalence of malnutrition in Sub distict Kedungtuban are above the average of other districts. This is the basis of why the research was conducted. Objective: To identify the relathionship between the complementary feeding energy intake and nutritional status of infants aged 6-12 months in Puskesmas Ketuwan, Kedungtuban, Blora, Central Java. Methods: This study is an observational study, using the cross-sectional design. Samples were infants aged 6-12 months residing in Puskesmas Ketuwan, Sub District Kedungtuban, Blora. The number of samples taken 60 infants and taken by proportional cluster random sampling. Interview respondents were mothers / families / caregivers of infants (research subjects). The statistical test used was Fisher's Exact Test. Results: Type MP-ASI consists of fruit (3.3%), manufacturing (5%), traditional (1.67%), MP-ASI mixture manufacturer and fruits (6.67%), a mixture of traditional and complementary feeding manufacturer (5%), a mixture of traditional and fruit (3.33%), a mixture consisting of three components: fruit, traditional food, and manufacturers (75%). Energy intake in infants with good nutritional status gets more energy intake than infants with malnutrition status 114.63 kcal, with the rate of energy intake of infants with good nutritional status is higher than 12.63% of infants with malnutrition. The significancy of first timing of complementary feeding with nutritional status of infants is 0,85, and the significancy of frequency of complementary feeding with nutritional status of infants is 0,43. The significancy of relationship between energy intake of complementary feeding with nutritional status of infants aged 6-12 months in Puskesmas Ketuwan, Kedungtuban, Blora is 0.04 (p <0.05). Conclusion: MP-ASI pattern of a mixture of fruit, food manufacturers and traditional food is the highest number of complementary feeding. Energy intake in infants with good nutritional status gets more energy and protein intake than infants with malnutrition status. There is not significant relationship between first timing of complementary feeding and nutritional status of infants. There is not a significant relationship between frequency of complementary feeding and nutritional status of infants. There is a significant relationship between energy intake of complementary feeding and nutritional status of infants aged 6-12 months in Puskesmas Ketuwan, Kedungtuban, Blora.